2009
DOI: 10.1007/s00384-009-0697-z
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre review of lymph node harvest in colorectal cancer

Abstract: Over 50% of all colorectal cancer specimens contain fewer than 12 lymph nodes despite clear national guidelines. This is of particular importance to Dukes B cancers where over 53% of cases may be understaged and not offered adjuvant therapy. Significant variation exists between hospitals within the same region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Lastly in England, Johnson 40 and Mitchell 41 have recently pointed out that the limit of 12 nodes was not reached between 33 and 50% of colorectal cancer cases. In view of these data, we deem it reasonable to say that the value of p-CEA acquires further importance.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly in England, Johnson 40 and Mitchell 41 have recently pointed out that the limit of 12 nodes was not reached between 33 and 50% of colorectal cancer cases. In view of these data, we deem it reasonable to say that the value of p-CEA acquires further importance.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, in reports published between 2005 and 2010, despite the "dense forest of articles" [18], the lymphadenectomy was considered inadequate in percentages varying between 63% and 48% of cases [18,19] and similar results were reported in Germany and England [20][21][22].…”
Section: Discussionmentioning
confidence: 74%
“…This phenomenon has been observed by several authors in different entities. 7,9 The analysis of this systematical review revealed that the subgroup of patients with a lymph node count of 7-9 (median 7) disclosed the highest detection rates of N+ and lowest rate of N0 patients. which does not allow an appropriate "N0 + R0" subgroup analysis; the population with obviously the best prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…(0-2.5) 7 (6)(7)(8)(9)(10)(11) Legend: Reg= Regional, Ext= Extended, LAD= Lymphadenecomy, LNC= Lymph node count, * Average, ** Information for all entities included, ***Lymph node station according to Japanese Gastric Cancer Association M A N U S C R I P T…”
Section: Authormentioning
confidence: 99%
See 1 more Smart Citation